2016
DOI: 10.1002/adma.201505218
|View full text |Cite
|
Sign up to set email alerts
|

Mogul‐Patterned Elastomeric Substrate for Stretchable Electronics

Abstract: A mogul-patterned stretchable substrate with multidirectional stretchability and minimal fracture of layers under high stretching is fabricated by double photolithography and soft lithography. Au layers and a reduced graphene oxide chemiresistor on a mogul-patterned poly(dimethylsiloxane) substrate are stable and durable under various stretching conditions. The newly designed mogul-patterned stretchable substrate shows great promise for stretchable electronics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
110
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(119 citation statements)
references
References 57 publications
(63 reference statements)
2
110
0
Order By: Relevance
“…The approach toward fabrication of stretchable OLEDs is schematically described in Figure . It includes fabrication of 3D‐MSES with stress‐adaptable characteristics (the detailed fabrication process and the characteristics of the 3D‐MSES were presented in a previous report) . The 3D‐MSES contains bumps and valleys, which are regularly positioned in a hexagonal close‐packed structure which helps to generate the highest number of the bumps and valleys per unit area.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach toward fabrication of stretchable OLEDs is schematically described in Figure . It includes fabrication of 3D‐MSES with stress‐adaptable characteristics (the detailed fabrication process and the characteristics of the 3D‐MSES were presented in a previous report) . The 3D‐MSES contains bumps and valleys, which are regularly positioned in a hexagonal close‐packed structure which helps to generate the highest number of the bumps and valleys per unit area.…”
Section: Resultsmentioning
confidence: 99%
“…The key factors that directly affect the performance of the OLED included the surface characteristics of surface defects and the roughness of 3D‐MSES. The 3D‐MSES was generated by replication from a master mold by a double photolithography process . Therefore, the fabrication of 3D‐MSES also replicates the defects and roughness on its surface.…”
Section: Resultsmentioning
confidence: 99%
“…[45] The sensor can be integrated into a watch-type wearable gas monitor, as shown in Figure 6g. Besides flexible gas sensors, stretchable gas sensors were also demonstrated by Lee et al [173] Stable NO 2 sensing performance under 30% strain was observed for rGO based gas sensors.…”
Section: Wearable Environmental Sensorsmentioning
confidence: 96%
“…In a CNT/poly(vinyl alcohol) (PVA) fiber based resistive sensors, high humidity level can swell the filament, decrease the intertube distance of CNTs and thus decrease the resistance of the CNT/PVA fibers. [55] To track the gas concentration for personal wellness and security surveillance, wearable gas sensors based on graphene, [32] rGO, [45,173] ZnO NPs, [174] AgNW-graphene, [175] CNT/SnO 2 NW hybrid film, [31] and polypyrrole NPs [176] were developed to detect the concentration of gases such as nitrogen dioxide (NO 2 ), [31,32,173] ammonia (NH 3 ), [176] hydrogen sulfide (H 2 S), [45] hydrogen (H 2 ), [45] ethanol (C 2 H 5 OH), [45,174] acetic acid (CH 3 COOH), [176] dimethyl methylphosphonate (C 3 H 9 O 3 P, DMMP), [175] acetone (CH 3 COCH 3 ), [175] methanol (CH 3 OH), [175] and tetradecane (C 14 H 30 ). [175] Increase or decrease in resistance is typically detected, depending on whether the gaseous stimulus is an electron donator or an electron acceptor.…”
Section: Wearable Environmental Sensorsmentioning
confidence: 99%
“…Despite the promise of these systems, only limited successful examples of stretchable sensors that perceive force and chemical stimuli have been reported. [5][6][7] To achieve high-performance artificial e-skin, the directional design and fabrication of conductive sensing channel materials are prerequisites. Tailored materials in the sensing channel with specific nanostructures can meet critical requirements such as enhanced sensitivity, stretchability and mechanical stability.…”
mentioning
confidence: 99%